Youth Receptivity to FDA's The Real Cost Tobacco Prevention Campaign: Evidence From Message Pretesting. Issue 11 (1st November 2016) - Zhao, Xiaoquan; Alexander, Tesfa N.; Hoffman, Leah; Jones, Chaunetta; Delahanty, Janine; Walker, Matthew; Berger, Amanda T.; Talbert, Emily
Abstract : In February 2014, the Food and Drug Administration launched The Real Cost, a national youth tobacco prevention campaign. This article examines youth receptivity to potential campaign ads using data from 3 message pretesting studies featuring the same design and consistent instrumentation. A total of 3, 258 adolescents ages 13–17 were randomized to either an ad-viewing condition or a no-exposure control condition. Perceived ad effectiveness, smoking-related beliefs, and attitudes were measured as outcome variables. The sample consisted of both experimental smokers (58%) and current nonsmokers at risk for cigarette initiation (42%). A total of 14 ads were tested across the three studies. Participants who viewed the ads generally considered them to be effective (with a mean perceived ad effectiveness score of 3.66 on a scale from 1 to 5). Compared to those in the control condition, participants in the ad-viewing condition reported stronger beliefs about the health risks of smoking ( p  < .001), a greater likelihood that smoking would lead to loss of control in life ( p  < .001), and more negative attitudes toward smoking ( p  < .001). Responses to campaign ads were largely consistent between experimenters and at-risk nonsmokers. Implications of the findings for the campaign are discussed.